Effectiveness of Belfast Regime on Flexion Tendon Injury Zone V Using Tam Scoring - Maha Farhina, Bushra Zulfiqar, Maryam Noor, Saba Kiran, Faisal Akhlaq Ali Khan, Shafaatulllah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of the study is to evaluate the effectiveness of belfast protocol in Flexion tendon injury of zone v through TAM scoring. Methodology: A prospective study will be directed to find out the outcome of Belfast protocol in flexor tendon injury in the premises of plastic surgery ward civil hospital Karachi, we were use non probability sampling technique to enlist the patient .we were systematized a well-designed questionnaire and through TAM scoring to measure the intervention outcome in term of functional ADL. Results: The results showed that there were 76% male and 24% female patients were affected. Most of the injury happened at work in 29% and at home 21% patients.44% patients were (21-30 ) years of age , 36% patients were (31-40) 4% of patients were (41-50) , 2% of patients were (51-60). TAM Score was observed that total 22 patients had excellent outcome (Score 100), 19 patients had good outcome (Score 75-99), 4 patients had fair outcome (score50-74 ) and only 5 patients had poor outcome. It was observed that treatment was effective in 45 patients because their TAM Score was >50 and in only 5 patients the treatment was ineffective because their TAM Score was <50. Conclusion: We concluded that belfast regime (early passive and active range of motion of fingers the rate of tendon adhesion and rupture rate was very low and gave good result , most commonly men was affected with the injury that’s 76% and commonly injury happened at work place by accident . There is no standard protocol and therapist must communicate with the surgeon and patients before selecting an appropriate therapy program.. Keywords : Rehabilitation ,Flexor injury , Zone V, Early mobilization ,Belfast technique.